Micromorphological evidence for subglacial multiphase sedimentation and deformation during overpressurized fluid flow associated with hydrofracturing. (24th May 2012) - Phillips, Emrys; Everest, Jez; Reeves, Helen
<x xml:space="preserve">Abstract</x> Hydrofracture systems are being increasingly recognized within subglacial to ice‐marginal settings and represent a visible expression of the passage of pressurized meltwater through these glacial environments. Such structures provide a clear record of the fluctuating hydrostatic pressure and of the resulting brittle fracturing of the host sediment/bedrock and the pene‐contemporaneous liquefaction and introduction of sediment‐fill. A detailed macro‐ and microstructural study of a hydrofracture system cutting Devonian sandstone bedrock exposed at the Meads of St John, near Inverness (NE Scotland), has revealed that this complex multiphase system was active over a prolonged period and accommodated several phases of fluid flow. The main conduits that fed the hydrofracture system are located along bedding within the sandstone, with the site of the wider, steeply inclined to subvertical, transgressive linking sections being controlled by the contemporaneous development of high‐angle fractures and normal faults, the latter occurring in response to localized extension within the bedrock. A comparison with published engineering hydraulic fracturing data indicates that the various stages of sediment‐fill deposited during a flow event can be directly related to the fluctuation in overpressure during hydrofracturing. A model is proposed linking the evolution of this hydrofracture system to the retreat of the overlying Findhorn glacier. The results of this study also indicate that the development and repeated reactivation of subglacial hydrofracture systems can have a dramatic effect on the permeability of the bed, influencing the potential for overpressure build‐up within the subglacial hydrogeological system, and facilitating the migration of meltwater beneath glaciers and ice sheets.